KAJIAN TINGKAT KEHILANGAN AIR DENGAN METODE NRW PADA PDAM TIRTA MEULABOH - Cut Suciatina Silvia (Universitas Teuku Umar, 2016)
Fresh water is a basic human need, hence, utilization of water needs was not limited. PDAM Tirta Meulaboh as local government water management company has not been able to meet the needs offresh water for the community, where the level of service that is produced is not running properly and optimally. Therefore, it is necessary to conduct a study related to the performance of the freshwater distribution service system, which the study aims to see the real condition of the water distribution network performance and problems of water loss that occurs in PDAM Tirta Meulaboh. The method that applied in this research is survey and quantitative methods which is supported by the primary data and secondary data. Based on the analysis results obtained that the discharge of average usage which is produced is just in 106.92 liters/person/day, where the shortage of fresh water needs of each customer on average >23 liters/person/day. Analysis of the rate of water loss in 2013 obtained that water loss reached 35.07% with water loss 783.967 m3/year or Rp 2.024.202.794/year. Based on the results of the NRW program analysis with ILI method obtained that ILI value of 38,5 with an average pressure of only 0,03 m. According to theTarget Table Matrix concluded that leakage or loss of water in zone service of Johan Pahlawan of PDAM Tirta Meulaboh belongs to the class D with ILI >16 and the leakage rate of >200 liters/connection/day. From these conditions, water loss that can not be cashed of 403.106 m3/year or 51,42% from water loss 783.967 m3/year.